The Functional State of the Myocardium in Patients with Ischemic Heart Disease, Diabetes Mellitus Type 2 and Cardiac Insufficiency - Horb Yu.; Strona V.; Komir I. (Львівський клінічний вісник)
Introduction. The problem of reducing mortality from cardiovascular disease in patients with type 2 diabetes mellitus remains a subject of particular attention in modern medicine and the whole society. Therefore, both fUrther study of the structural and functional state of the heart and blood vessels, as well as early diagnosis of myocardial lesions in patients with type 2 diabetes, which can give an opportunity to assess the risk of cardiovascular complications and to apply preventive measures against them, are relevant. The aim of the study. To review the scientific literature on the functional status of myocardium in patients with coronary heart disease (CHD), type 2 diabetes, and heart failure. Materials and methods. The content analysis, the systematic and comparative analysis method, the bibliosemantic method of studying the current scientific researches on the topic of functional status of the myocardium in patients with type 2 diabetes were used. Sources were searched in the medical science databases PubMed NCBI, Medline, Research Gate for keywords ischemic heart disease, type 2 diabetes, heart failure, comorbidity, myocardial functional status, cardiac and vascular remodeling. 153 sources in English and Ukrainian languages have been analyzed. The sources, which highlight the clinical and pathogenetic features of the functional status of the myocardium in patients with type 2 diabetes, were selected. Results. Type 2 diabetes and its complications, which are often myocardial disorders, lead to the early disability of people of mainly working age. The pathogenesis of myocardial disorders in patients with type 2 diabetes involves 3 major mechanisms: cardiomyocyte damage, microcirculatory and neurovegetative disorders. Type 2 diabetes in the myocardium causes dystrophic changes, the pathogenesis of which is characterized by the primary impaired metabolism of cardiomyocytes, microangiopathy, neuropathy, as well as a decrease in the susceptibility of the left ventricular myocardium, which is associated with the development of interstitial fibrosis and disturbed fibrotic fibrosis. In patients with diabetic cardiomyopathy, all conditions for the development of disturbances of heart rhythm and conduction are created, the number and severity of arrhythmias depend on the severity of type 2 diabetes.The degree of myocardial injury in patients with type 2 diabetes is determined not only by the severity of atherosclerotic changes in the coronary arteries, but also by specific changes characteristic of complications of type 2 diabetes, in particular, by microangiopathy. Gender analysis showed a significant increase in left ventricular and left atrial dimensions, with a more pronounced decrease in myocardial systolic function in men with type 2 diabetes, obesity, and postinfarction cardiosclerosis compared with women regardless of age. The earliest sign of myocardial damage in type 2 diabetes is the appearance of diastolic dysfunction of the left ventricle with subsequent dilatation of its cavity and the development of progressive heart failure and heart rhythm disorders. Clinical signs in patients with coronary artery disease on the background of type 2 diabetes are often nonspecific and diagnosis is not timely. Therefore, the issue of early diagnosis of diabetic heart and treatment principles is not relevant. The main factors of formation of cardiovascular diseases in type 2 diabetes, first of all, atherosclerosis and coronary heart disease (CHD) are considered, pathogenetic relationship between these comorbid conditions is analyzed. The modern views on mechanisms of impaired functional state of the myocardium and accelerated remodeling of heart and blood vessels in patients with coronary heart disease in combination with type 2 diabetes are presented. The significant role of the combination of these diseases in the formation of macro- and microvascular complications, the development of chronic heart failure (CHF), as well as a significant increase in the risk of acute cardiac events and mortality, which determines the importance and relevance of the problem of improving treatment and preventive measures. Conclusions. The main purpose of the examination of patients with coronary heart disease and concomitant diabetes mellitus type 2 is to objectify the structural and functional state of the myocardium and peripheral vascular bed, which makes it possible to assess the risk of cardiovascular complications, to determine their diagnosis and to choose the optimal patient management tactics.